The use of inhaled nitric oxide to treat persistent pulmonary hypertension of the newborn in a tertiary public hospital in South Africa from 2010-2014: morbidity, mortality and cost - McAlpine, Alastair (Division of Neonatology, 2019)
Background and rationale: Inhaled nitric oxide (iNO) is recommended for the treatment of severe persistent pulmonary hypertension of the newborn (PPHN) because it reduces the need for extracorporeal membrane oxygenation (ECMO). There is insufficient evidence that iNO reduces mortality in the absence of ECMO. Although neonates in some South African public hospitals have access to iNO, ECMO is not available. Oral sildenafil can be effective in settings where iNO is not available, but its effect on outcome and cost of treatment in this setting have not been described. The literature review in the first part of this thesis describes five studies reporting short-term outcomes of PPHN in the absence of ECMO. No studies from South Africa were identified. Only two studies described outcomes after iNO – the coadministration of Sildenafil with iNO was only reported in one small study. There were insufficient published data to guide management in settings where ECMO is not available. Aim: To describe a cohort of term and near term neonates with PPHN who were treated with iNO, with or without sildenafil, in a tertiary neonatal unit in South Africa Objectives: (i) to describe the characteristics at birth, the clinical course, and shortterm outcomes; (ii) to determine if any variables were associated with mortality; (iii) to describe the relationship between the use of sildenafil and cost of care, represented by the duration of intubation and iNO use; and (iv) to describe the frequency of sildenafil prescription. Methods. A retrospective review was carried out on folders of neonates with PPHN who were treated with iNO in Groote Schuur Hospital, Cape Town, South Africa, between January 2010 and December 2014. Results. Forty neonates were included – most were full term (85%). Meconium aspiration syndrome (MAS) was the commonest cause of PPHN (50%), followed by intrapartum hypoxia (20%), sepsis (17.5%), pulmonary hypoplasia (7.5%) and idiopathic (5%). Fourteen neonates (35%) died. Pulmonary hypoplasia and pneumothorax were associated with mortality (p=0.037 and p=0.004 respectively). An FiO2 of 1.0 and an iNO dose of ≥ 20 ppm at 24 and 48 hours respectively, both predicted death (specificity 89% vs. 100%, sensitivity 67% vs. 43% and p=0.003 vs. p=0.007 respectively). Sildenafil was prescribed more often after 2011 (83% vs. 65%) and was associated with increased survival (p=0.018) – early administration was associated with a shorter time to extubation (p=0.012) and a shorter course of iNO (p=0.044). Conclusion. The treatment of PPHN with iNO in the absence of ECMO was associated with high mortality, particularly in neonates with congenital lung abnormalities. The FiO2 and iNO requirements at 24 and 48 hours respectively could be used to identify neonates who are unlikely to benefit from continued treatment. Sildenafil was prescribed with increasing frequency during the study. The combination of iNO with sildenafil was associated with more cost-effective care and improved short term outcomes. These findings provide a potential basis for costsaving measures and resource allocation.